2018
DOI: 10.22159/ijpps.2018v10i1.22686
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Iron Oxide Nanoparticles for Treatment of Iron Deficiency Anemia

Abstract: Objective: The objective of this research was to formulate and evaluate iron oxide nanoparticles for treatment of iron deficiency anemia (IDA). Methods:Iron oxide nanoparticles were prepared by co-precipitation method and stabilized by coating with folic acid or chitosan. The prepared nanoparticles were characterized in vitro for morphology, particle size, zeta potential, crystallinity and ultraviolet-visible (UV-Vis) absorption. In vivo studies were performed to evaluate the efficacy of the prepared nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…By treatment with iron oxide nanoparticles or ferrous sulfate, there was no significant change in the blood indices than control. Our result matched with Hashem et al [7] who reported a significant increase in red blood cell indices in iron oxide nanoparticles group when compared to anemic group which may be due to the effectiveness of iron oxide nanoparticles in treatment of anemia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By treatment with iron oxide nanoparticles or ferrous sulfate, there was no significant change in the blood indices than control. Our result matched with Hashem et al [7] who reported a significant increase in red blood cell indices in iron oxide nanoparticles group when compared to anemic group which may be due to the effectiveness of iron oxide nanoparticles in treatment of anemia.…”
Section: Discussionsupporting
confidence: 91%
“…It is composed of 10 % sunflower oil, 4% salt mixture, 1% vitamin mixture, 2 % choline chloride, 12 % DL-methionine and cornstarch up to 100 g [7].…”
Section: Preparation Of Iron-free Basal Dietmentioning
confidence: 99%
“…Iron deficiency anemia is a most common nutritional disorder and serious public health concern in developing countries, and maternal iron deficiency anemia increases the incidence of maternal mortality and morbidity as well it also increases the incidence of fetal growth retardation, premature delivery, and neurodevelopment of the fetus [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, IONP have many applications in medicine including: enhance targeting for drug delivery [32], hyperthermia to complement treatment of various tumor types [33], promote transient opening of the blood-brain barrier [34], enhance MRI contrast for medical imaging [35]. In addition, IONP-based drugs are FDA-approved to treat iron deficiency [36,37]. The ovary is the most important and arguably the most delicate female reproductive organ that feeds from the main artery which in turn stems from ovarian branches of the aorta [13].…”
Section: Discussionmentioning
confidence: 99%